Brazil - Mazzei, L.; Rocha, C. (Comparative elite sport development. Systems, structures and public policy, 2025)
Brazil is a country with continental dimensions (8.51 million km2 - all the countries of the European Union could fit inside Brazil's borders twice over) and a population characterised by diversity. Throughout history people from different nationalities have migrated to Brazil. Immigration had a peak during the end of the 19th century and the first half of the 20th century, mainly as a consequence of incentives from the Brazilian government and the global context. At that time, the country already had a large population of African and Portuguese descendants from the time of colonisation. The interaction between immigrants and native peoples gave birth to a mixed Brazilian population (Fausto, 2012). In the 21st century, immigration continues, albeit in a more limited and spread-out manner. The cultural diversity of the population has had an important impact on all aspects of social life in the country, including sport and how it has been promoted and developed at all levels. Specifically relevant for this chapter, the Brazilian elite sport model has been strongly influenced by European models to organise and support competitive sport in the country.